HIV Vulnerability Among Survival Sex Workers Through Sexual Violence and Drug Taking in a Qualitative Study From Victoria, Canada, With Additional Implications for Pre-exposure Prophylaxis for Sex Workers - Benner, Bryan Eric (Frontiers in Sociology, 2022)
Objective: This qualitative study investigates how social and structural forces mediate vulnerability to HIV infection and transmission among survival sex workers, their clients, and their non-commercial, intimate partners – with especial focus on sexual violence and drug taking. Method: I employed an adapted grounded theory approach to conducting and analyzing (n=9) open-ended, in-depth interviews with a convenience sample of currently working (and recently exited) survival sex workers from a community setting in Victoria, Canada. Findings: Participants revealed important contexts and conditions under which they were vulnerable to HIV infection. At the behavioural level, participants were aware of how HIV could be transmitted (condomless sex and sharing drug equipment), yet participants voiced strongly how structural and systemic features (for instance, client violence, the need for drugs, and ‘bad date’ referrals) could squeeze and constrain their agency to take up safer practices, mediating their optimal HIV health and safety. Some participants reported strained relationships with police because of previous drug involvement. Conclusion: Survival sex workers constitute a health population vulnerable to HIV infection, and ensuring there could be a supportive (outreach) community replete with HIV resources is paramount. The availability of safer sex and drug equipment play important roles in HIV behavioural prevention efforts. However, uptake of pre-exposure prophylaxis (PrEP) at no cost in the Canadian province of British Columbia could be an important and beneficial structural intervention for non-injection drug taking cis-female sex workers in this study who are presently ineligible for no cost PrEP.